ISO 14001 EMS : Implementation issues. - Tan, Hui Li. (2008)
There have been many significant events in the field of environmental management. However, most pale in comparison is the addition of environmental management into the International Organization for Standardization (ISO) certification system. Our project features local cases, experiences and examples, describing actual difficulties faced in pursuing ISO 14001 certification.